On the Hayman-Wu theorem for quasilines - Maimeskul, V. V.; Маймескул, В. В.; Маймескул, В. В. (Institute of Mathematics, NAS of Ukraine, 1996)
For a function ω, we establish a condition sufficient for the sum ∑i, ω(diam φ(L i )) to be finite for any quasiconformal curve L i , simply connected domain Ω, and a function φ which conformally and univalently maps this domain onto the unit disk. Here, L i denote the components of Ω∩L.